La casa de cristal : hacia una subversión normativa de la economía / Juan Manuel Martínez Hernández, Luis Martínez de Velasco - Martínez de Velasco, Luis; Martínez Hernández, Juan Manuel (Colección Ciencia; 181. Serie economía)
Bibliografía: p. 235-239